Defining Conditional Belonging: The Case of Female Science Fiction Fans. (October 2021) - Yodovich, Neta
This article offers a rigorous conceptualisation of an undeveloped sociological concept: conditional belonging. It implements and develops conditional belonging in the setting of everyday life by examining female fans of science fiction. Based on 30 in-depth interviews with female fans of Doctor Who and Star Wars, this study defines conditional belonging as a liminal state in which new members are constructed as a threatening 'other' and required to demonstrate conformity to the community. Having to align with values established by veteran members disrupts the ability of those who conditionally belong to perceive their identities as authentic. Conditional belonging is explored in offline and online settings, exposing the tactics used online by female fans to ensure their belonging. Through demonstrating the ways in which conditional belonging is cultivated and enforced, this article contributes to a nuanced understanding of belonging, not as a binary condition, but a multi-layered, complex one.